PENGARUH IKLIM ORGANISASI DAN DISIPLIN KERJA TERHADAP EFEKTIVITAS ORGANISASI DI KANTOR CAMAT TOMA KABUPATEN NIAS SELATAN - Witisari Variyani Duha (PARETO : Jurnal Riset Bisnis dan Manajemen, 2024)
The objective of this study is to assess the impact of the organisational environment and work discipline on the effectiveness of the Toma Subdistrict Office in the South Nias Regency. This study is of a quantitative nature. The data for this study is derived from a questionnaire administered to workers. The research population consists of 30 respondents, which also serves as the sample size. The used methodology for data analysis is multiple regression analysis. The researcher believes that there is a significant impact of organisational environment and work discipline on organisational effectiveness in the Toma Subdistrict Office, South Nias Regency, based on the findings of hypothesis testing study. This conclusion is supported by the fact that the calculated F value (41,365) is more than the critical F value (3,343). The recommendations of this study are as follows: (1) In order to enhance employee attendance, it is advised to provide warnings to workers who are missing. (2) It is important to oversee the execution of duties performed by workers and guide them or provide remedies if their work deviates, ensuring that all work is conducted in compliance with established regulations.